Seed germination capability of four endemic species in the Central Apennines in Italy: relationship between seed size and germination capability - Frattaroli, Anna Rita; Di Martino, Luciano; Di Cecco, Valter; Catoni, Rosangela; Varone, Laura; Di Santo, Marco; Gratani, Loretta (Lazaroa, 2013)
Seed germination capability of Adonis distorta, Androsace mathildae, Aquilegia magellensis and Campanula fragilis subsp. cavolinii endemic species of the Central Apennines in Italy were analyzed. Seed traits varied significantly among the considered species. In particular, seed volume was the largest in Ad. distorta (91.642 ± 16.851 mm3) and the lowest in C. fragilis subsp. cavolinii (0.029 ± 0.008 mm3). The seed coat thickness ranged from 31 ± 10 µm in Ad. distorta to 9 ± 1 µm. in C. fragilis subsp. cavolinii. Seed coat was brown colored in An. mathildae, dark brown in Aq. magellensis, light brown in Ad. distorta and cream colored in C. fragilis subsp. cavolinii. Pre-treatments were carried out to improve seed germination. Seed germination did not happen in Ad. distorta and An. mathildae in response to the applied treatments (i.e., 0, 250, 500 ppm gibberelic acid, GA3) and cold-wet stratification. A 65 % increase of germination was observed after the pre-treatment with 500 ppm GA3 in Aq. magellensis which could be justified by an endogenous non-deep physiological dormancy. The final germination percentage increased by 26% in Aq. magellensis and decreased by 89% in C. fragilis subsp. cavolinii after the cold-wet stratification treatment. The obtained results may be used to define a germination protocol in reinforcement projects of the wild populations as a mean of reducing the extinction risk of these endemic species.